Reflexões sobre estilos de liderança feminina e masculina no contexto universitário - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The objective of this study was to analyze the perception of staff regarding the leadership orientation of men and women who stand out in the university environment. This is a descriptive, quantitative research study, conducted using the survey method. Data collection involved 37 staff members, including faculty and administrative technicians, and used a structured questionnaire consisting of socio-demographic questions and the leadership heteroevaluation scale by Mourão, Faiad, and Coelho Junior (2016). The results indicated that, in general, the participants perceive balanced leadership practices, combining concern for people and focus on results, regardless of the gender of the supervisor. The comparative analysis revealed no statistically significant differences between the perceptions of men and women, nor between faculty and technicians, regarding the evaluated behaviors. However, differences were identified between staff members who hold management positions and those who do not, particularly in items related to performance monitoring and emphasis on collective work. The findings demonstrate that the institutional context and the role performed influence leadership perceptions more than the leader's gender, suggesting that UNIPAMPA's organizational culture contributes to management practices perceived as relatively homogeneous. The study reinforces the relevance of deepening discussions about leadership styles in the academic environment and points to the need for expanding investigations that consider gender, management, and institutional dynamics in an integrated manner
Reflections on female and male leadership styles in the university context
Reflexiones sobre los estilos de liderazgo femenino y masculino en el contexto universitario
Keywords: Liderança; Gênero; Universidades; Leadership; Gender; Universities; Staff; Perceptions; Liderazgo; Género; Servidores; CIENCIAS SOCIAIS APLICADAS